PEMBUATAN PUPUK ORGANIK CAIR SEBAGAI UPAYA PENGURANGAN SAMPAH DI KELURAHAN KURAO PAGANG KOTA PADANG - Calysta Deli Ad'hani; Bayu Muhammad Ilham; Kiki Ervina; Zulkarnaini Zulkarnaini (Jurnal Hilirisasi IPTEKS, 2024)
Household organic waste can be used as raw material to produce Liquid Organic Fertilizer (LOF) as an effort to reduce the amount of solid waste disposed of at Temporary Disposal Sites (TPS). The organic fertilizer produced can be reused in home gardens, such as for ornamental or fruit plants. In addition to being used as fertilizer, LOF can be used as a starter for making other organic fertilizers or as a decomposer in the production of compost. The community empowerment activities in making LOF aim to raise awareness of the potential of household waste as a valuable resource. Through a participatory approach, the community is encouraged to actively engage in the process of converting waste into LOF, which benefits agriculture and the environment. The empowerment and community development activities regarding the application of simple LOF production were conducted at RT 03 RW 09, Tanjung Berok, Kurao Pagang Sub-District, Padang City. The activities included socialization, education, and practical training on converting household organic waste into LOF using buckets as containers. As a result of these activities, the community gained increased knowledge in processing household organic waste into LOF and Microorganism Liquid (MOL), which can be used for fruit and ornamental plants in their yards and residential areas. The attendees realized the importance of protecting the environment by managing their household waste and avoiding disposing of waste into water channels.